2019
DOI: 10.1017/s0007114519003301
|View full text |Cite
|
Sign up to set email alerts
|

A simple cut-off for waist-to-height ratio (0·5) can act as an indicator for cardiometabolic risk: recent data from adults in the Health Survey for England

Abstract: The National Institute for Health and Care Excellence (NICE) has acknowledged the value of waist-to-height ratio (WHtR) as an indicator for ‘early health risk’. We used recent UK data to explore whether classification based on WHtR identifies more adults at cardiometabolic risk than the ‘matrix’ based on BMI and waist circumference, currently used for screening. Data from the Health Survey for England (4112 adults aged 18+ years) were used to identify cardiometabolic risk, indicated by raised glycated Hb, dysl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 66 publications
2
24
0
Order By: Relevance
“…BMI showed the strongest association in adults [18] or only in one sex [10,17,18], while associations for 3 parameters were nonsigni cant for men after adjustments [5]. However, others have reported results similar to ours [21,[23][24][25][26][27], including a cohort study in which subjects in the highest quartile of WHtR were 4.51 times more likely to have hypertension [28]. A systematic review also found that WHtR was the best parameter for predicting cardiometabolic risk factors, including hypertension [29].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…BMI showed the strongest association in adults [18] or only in one sex [10,17,18], while associations for 3 parameters were nonsigni cant for men after adjustments [5]. However, others have reported results similar to ours [21,[23][24][25][26][27], including a cohort study in which subjects in the highest quartile of WHtR were 4.51 times more likely to have hypertension [28]. A systematic review also found that WHtR was the best parameter for predicting cardiometabolic risk factors, including hypertension [29].…”
Section: Discussionsupporting
confidence: 72%
“…There were no signi cant differences in the predictive capacities of WC, BMI, and WHtR between men and women [31]; and the predictive values of BMI, WC, and WHtR were found to differ signi cantly between men and women [5], with a better performance in the latter [34]. WHtR has also been proposed as the best predictor of PWV or hypertension [25,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was reported that WHtR identified people with early health risks better than a matrix that combined BMI and WC. 26,27 In a study that compared the predictive ability of multiple anthropometric indices and other parameters, TyG-WC was reported to be the best. 28 But TyG-WHtR was not included for comparison in their study.…”
Section: Fig 1 Roc Curves Formentioning
confidence: 99%
“…Of BMI and waist‐to‐height ratio (WHtR), the latter is a better indicator of cardiometabolic risk (Ashwell et al . 2012; Gibson & Ashwell 2019) as it measures central obesity. Data from other populations on associations with egg consumption are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Although egg consumers reported higher energy intakes than non-consumers, indices of body weight or obesity were either similar for consumers and nonconsumers, or significantly lower in the case of women. Of BMI and waist-to-height ratio (WHtR), the latter is a better indicator of cardiometabolic risk (Ashwell et al 2012;Gibson & Ashwell 2019) as it measures central obesity. Data from other populations on associations with egg consumption are conflicting.…”
Section: Cardiometabolic Risk Factorsmentioning
confidence: 99%